Politiche e aiuti allo sviluppo: che cosa abbiamo imparato? - DOI: 10.5752/P.2316-1752.2009v16n18/19p265 - Berloffa, Gabriella; Folloni, Giuseppe; Wartensee, Ilaria Schnyder von (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This paper analyzes and discusses the empirical evidence of low effectiveness in the growth of policies of investment in physical and human capital based on international aid (§ 1 and 2). Reasons for that are linked both to the limits of analytical and econometric methods (§ 4) and to the existence of strong complementarities between different dimensions of the macroeconomic, social and institutional context (§ 3). Proposed new strategies to gain effectiveness in the development of projects and policies are critically discussed. Key words : Aid effectiveness; Growth policies; Institutions; Development.